Struggling for leadership authority : critical discourse analysis on Agus Harimurti Yudhoyono's political speech - Hetti Waluati Triana,; Maros, Marlyna; Kustati, Martin; Reflinaldi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to determine the socio-cognitive dimensions of Agus Harimurti Yudhoyono's (AHY) political speech as chairman of the Democratic Party (DP). The data was taken from AHY's speech entitled Konferensi Pers Ketua Umum Partai Demokrat Agus Harimurti Yudhoyono which was broadcasted on Agus Yudhoyono's YouTube channel. The lingual data was taken by using free listening techniques through the stages of transcription, reading and observation, sorting, storing and printing, re-reading, and determining the research subject. Meanwhile, non-lingual data was collected by using the Internet archive documentation method. The data were analysed through extra lingual matching technique, hermeneutics, and phenomenology. The analysis was carried out through the stages of data reduction, data display, conclusion, and verification. The findings showed that AHY represents himself as a democratic, caring, vigilant, thorough, careful, and committed to party sovereignty leader. The social cognition aspect of AHY is dominated by his background as a former military officer and his status as party leader. The narrative built in his speech was influenced by the poor results of DP in the last 2 elections, the low electability of DP, and conflicts at the internal level of DP. The sociocognitive analysis showed that AHY constructs leadership authority by representing himself as a selective, strategic, and political leader. The three characters he builds are the strong influence of his social cognition. Through his speech, AHY strives to fight for his leadership authority, both as the general chairman of the DP, and for the wider community.